HUBUNGAN DERAJAT HIPERTENSI DENGAN STADIUM GAGAL GINJAL KRONIK DI UNIT HEMODIALISA RUMAH SAKIT BADAN PENGUSAHAAN BATAM TAHUN 2019-2020 - Fanany, Muhammad Azmi; Christina, Yani; Nasution, Tia Helvita Sari (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: Chronic Kidney Disease (CKD) is a progressive and irreversible kidney function disorder, in which the body is unable to maintain metabolism and fails to maintain fluid and electrolyte balance which results in an increase in urea.The risk factors for chronic kidney failure from hypertension are 3.2 times greater than those who do not have hypertension.The study aims to determine the relationship between the degree of hypertension and the stage of Chronic Kidney Failure in the hemodialysis unit at Badan Pengusahaan Batam Hospital in 2019-2020. Methods: The research design using analytic observational with a cross sectional approach in the Hemodialysis unit at the Badan Pengusahaan Batam Hospital in July 2023. The sample of this study was 95 patients with Chronic Kidney Failure who visited the Hemodialysis unit at Badan Pengusahaan Batam Hospital in 2019-2020selected by random sampling method. Analysis data using the Chi-Square correlation hypothesis test. Results: A total of 38 people (29.5%) respondents were in the age group 46-55 years and 48 people (50.5%) respondents were male, 62 people (65.3%) had grade 2 hypertension, 83 people(87.4%) of respondents had stage V chronic kidney failure. There was a significant relationship between the degree of hypertension and the stage of chronic kidney failure in patients at the Hemodialysis Unit RSBP Batam 2019-2020 (p=0.042). Conclusion: There is a significant relationship between the degree of hypertension and the stage of chronic kidney failure in patients at the RSBP Batam Hemodialysis Unit 2019-2020.